Promosi Kesehatan “Peduli Kesehatan Ginjal Remaja” Pada Peserta Didik SMA Muhammadiyah 2 Pontianak - Ridha Mardiyani; Almumtahanah Almumtahanah; Indri Erhwani; Imran Imran; Lidia Hastuti; Annisa Rahmawati (Jurnal Abdimas Kesehatan (JAK), 2022)
In this era of the industrial revolution 4.0, there are many teenagers whose attitudes and behavior are very caring. Health problems that are quite vulnerable to adolescents are fluid balance problems, because adolescents are more active in physical activities and there are also changes in metabolism in the body so that the need for fluids increases. The Indonesian Regional Hydration Study (THIRST) research suggests that 46.1% of the Indonesian population is mildly dehydrated, where adolescents have a higher level of mild dehydration (49.5%) than adults (42.5%), increase the risk of kidney stones, urinary tract infections, colon cancer, constipation, obesity, cerebral vascular stroke, and other disorders. The target of this activity is 23 students from SMA Muhammadiyah 2 Pontianak. The output of the activity is an increase in the cognitive aspects, attitudes and behavior of students in maintaining the health of the kidney organs. The activity was carried out with a Health Education approach. After being given health education, there was an increase in knowledge of the majority of students.